Hunting for the cause: Evidence for prion-like mechanisms in Huntington’s disease - Donnelly, Kirby M.; Coleman, Cevannah M.; Fuller, Madison L.; Reed, Victoria L.; Smerina, Dayna; Tomlinson, David S.; Pearce, Margaret M. Panning (Frontiers in Neuroscience, 2022)
The hypothesis that pathogenic protein aggregates associated with neurodegenerative diseases spread from cell-to-cell in the brain in a manner akin to infectious prions has gained substantial momentum due to an explosion of research in the past 10-15 years. Here, we review current evidence supporting the presence of prion-like mechanisms in Huntington’s disease (HD), an autosomal dominant neurodegenerative disease caused by expansion of a CAG repeat tract in exon 1 of the huntingtin (HTT) gene. We summarize information that has been gained from human studies and in vivo and in vitro models of HD that provide strong evidence for prion-like features of the mutant HTT (mHTT) protein, including potential involvement of molecular features of mHTT seeds, synaptic structures and connectivity, endocytic and exocytic mechanisms, tunneling nanotubes, and phagocytic glial cells in mHTT propagation through the brain. We discuss mechanisms by which mHTT aggregate spreading and neurotoxicity could be causally linked and potential benefits of targeting prion-like mechanisms in the search for new disease-modifying therapies for HD and other fatal neurodegenerative diseases.